Induction of Regulatory Properties in the Intestinal Immune System by Dimethyl Fumarate in Lewis Rat Experimental Autoimmune Neuritis - Pitarokoili, Kalliopi; Bachir, Hussein; Sgodzai, Melissa; Grüter, Thomas; Haupeltshofer, Steffen; Duscha, Alexander; Pedreiturria, Xiomara; Motte, Jeremias; Gold, Ralf (Frontiers in Immunology, 2019)
Objective: Dimethyl fumarate (DMF) exerts immunomodulatory and neuroprotective effects in the animal model of experimental autoimmune neuritis (ΕΑΝ) in the Lewis rat. DMF has been shown to modulate gut microbiota in veterinary medicine, however the effects of oral DMF on the gut-associated lymphoid tissue (GALT) remain unknown. Methods: Lewis rats were treated orally twice daily with DMF up to day 10 after immunization with immunogenic P2 peptide. Histological, flow cytometric and RT-PCR analyses of the GALT (intraepithelial layer, lamina propria and Peyer patches) in duodenum, jejunum and ileum were performed ex vivo. Moreover, cell transfer experiments were used to examine the protective effects of GALT regulatory T cells of the Peyer patches. Results: In the upper layers of duodenum, DMF induced a reduction of the toll-like receptor 4 (TLR4) mRNA expression. This was combined by a decrease of the pro-inflammatory lamina propria IFN-γ mRNA expression. In the ileum, we detected an immunoregulatory phenotype characterized by an increase of FoxP3 mRNA expression and of the nuclear factor (erythroid-derived-2)- like 2 (Nrf2) downstream molecule heme oxygenase-1 (HO-1) mRNA. Finally, CD4+ CD25+ regulatory T cells were increased in the Peyer patches. In vivo, the protective effect of these regulatory cells was verified by cell transfer into recipient EAN rats. Conclusions: Our results identified a novel immunomodulatory effect of DMF through the different regions and layers of the small intestine, which led to an increase of regulatory T cells, exerting a protective role in experimental neuritis.